How Can Renting Accommodation Contribute To The Circular Economy? - Azis Musthofa; Rijanta, R. (Journal of World Trade Studies, 2022)
Yogyakarta is a tourist destination with various attractions and tourist attractions objects. The high number of tourists has consequences for providing facilities such as accommodation, restaurants, travel agents, and various other supplies. Developments in technology and information have led to changes in people's consumption patterns. The emergence of various platforms that support various economic activities has contributed to the tourism sector in Yogyakarta. Airbnb is a platform that has increased the utilization of home assets, either partially or entirely, for rent to those in need. Every peak month, the need for large rooms in Yogyakarta has occupied almost all tourist accommodation rooms. This condition is an opportunity for sharing economy actors. This study aims to discuss to what extent renting out a place to live contributes to a circular economy. Literature study and secondary data analysis are used to explain this phenomenon. The activities of various dwellings in the sharing economy aim to increase the utilization of unused assets by renting them out to the needy. This concept supports the goals of a circular economy because previously unused home assets can be optimized using the platform. Although Airbnb has yet to be able to make a significant contribution to meeting the needs of tourist accommodation rooms in Yogyakarta, its various advantages have been able to meet the needs of tourists with specific preferences.